Novel Heterozygous Sequence Variant in the HOXD13 Gene Underlie Non-syndromic Syndactyly - Safdar Abbas; Farooq Ahmad; Misbah Kanwal; Annum Sultan; Gulab Said; Muhammad Umair (Journal of Biochemical and Clinical Genetics)
Background: The term "Syndactyly" referred to an inherited deformity of the hand or foot marked by persistence of the webbing between adjacent digits that are more or less completely attached and mostly inherited in an autosomal dominant manner. Pathogenic variants in the HOXD13 (Homeobox D13) gene, located on chromosome 2q31.1, have been associated with syndactyly type 5, brachydactyly type D, E and synpolydactyly type 1 phenotypes. Objectives: A Pakistani inbreed was recruited from the remote area of the country was added in the study and aimed to clinically and genetically characterize the syndactyly as marked abnormal feature observed. Methodology: Whole exome sequencing coupled with Sanger sequencing was carried out to uncover the disease associated variant/s followed by 3D protein modeling to check variant related effect on protein level. Results: WES data analysis revealed a novel-HOXD13 gene missense variant (c.969G>T; p.Trp323Cys) that might explain the disease phenogenesis. 3D protein modeling of the normal and mutant protein predicated high level changes that might compromise the ultimate function of the protein. Conclusion: Our findings extend the mutation spectrum of HOXD13 gene and also provided additional evidence that HOXD13 play an important role in limbs development. [JBCGenetics 2023; 6(2.000): 091-096]